The mathematical brain at rest. (February 2023) - Wilkey, Eric D; Gupta, Ira; Peiris, Ashini; Ansari, Daniel
Abstract : In this review, we consider the scope of work that uses resting-state functional connectivity (RSFC) analyses of functional magnetic resonance imaging data relevant for understanding the mathematical brain. After briefly introducing this technique and its utility, we identify three main themes this research has focused on: (1) using RSFC to identify patterns in brain connectivity that relate to individual differences in math ability or may be associated with math learning difficulties, (2) the use of RSFC to understand the effects of math training or intervention on the brain, and (3) insights that RSFC provides regarding the development and plasticity of mechanisms of the mathematical brain. The major contributions within each research theme are discussed alongside unresolved issues in RSFC study design related to understanding the development of math skills. Highlights: 26 studies were identified relating resting-state fMRI to mathematical cognition. We identify the advantages of this technique for understanding the mathematical brain. Themes include relations to math skills, intervention studies, and understanding mechanisms. Key contributions from the literature and methodological shortcomings are discussed.